LYN- and AIRE-mediated tolerance checkpoint defects synergize to trigger organ-specific autoimmunity - Proekt, Irina; Miller, Corey N.; Jeanne, Marion; Fasano, Kayla J.; Moon, James J.; Lowell, Clifford A.; Gould, Douglas B.; Anderson, Mark S.; DeFranco, Anthony L. (The Journal of Clinical Investigation, 2016)
Studies of the genetic factors associated with human autoimmune disease suggest a multigenic origin of susceptibility; however, how these factors interact and through which tolerance pathways they operate generally remain to be defined. One key checkpoint occurs through the activity of the autoimmune regulator AIRE, which promotes central T cell tolerance. Recent reports have described a variety of dominant-negative AIRE mutations that likely contribute to human autoimmunity to a greater extent than previously thought. In families with these mutations, the penetrance of autoimmunity is incomplete, suggesting that other checkpoints play a role in preventing autoimmunity. Here, we tested whether a defect in LYN, an inhibitory protein tyrosine kinase that is implicated in systemic autoimmunity, could combine with an Aire mutation to provoke organ-specific autoimmunity. Indeed, mice with a dominant-negative allele of Aire and deficiency in LYN spontaneously developed organ-specific autoimmunity in the eye. We further determined that a small pool of retinal protein–specific T cells escaped thymic deletion as a result of the hypomorphic Aire function and that these cells also escaped peripheral tolerance in the presence of LYN-deficient dendritic cells, leading to highly destructive autoimmune attack. These findings demonstrate how 2 distinct tolerance pathways can synergize to unleash autoimmunity and have implications for the genetic susceptibility of autoimmune disease.